College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.7 - Combining Functions - 2.7 Exercises - Page 252: 11


$(f+g)(x)=x^{2}-4x+5 \rightarrow$ $D=(-\infty,+\infty)$ $(f-g)(x)=-x^{2}+2x+5 \rightarrow$ $D=(-\infty,+\infty)$ $(f.g)(x)=-x^{3}+8x^{2}-15x \rightarrow$$D=(-\infty,+\infty)$ $(\frac{f}{g})(x)=\frac{5-x}{x^{2}-3x}\rightarrow$ $D=(-\infty,0)\cup(3,+\infty)$

Work Step by Step

We are given $f(x)=5-x$ and $g(x)=x^{2}-3x$ $(f+g)(x)=x^{2}-4x+5 \rightarrow$ $D=(-\infty,+\infty)$ $(f-g)(x)=-x^{2}+2x+5 \rightarrow$ $D=(-\infty,+\infty)$ $(f.g)(x)=(5-x)(x^{2}-3x)=5x^{2}-15x-x^{3}+3x^{2}=-x^{3}+8x^{2}-15x \rightarrow$$D=(-\infty,+\infty)$ $(\frac{f}{g})(x)=\frac{5-x}{x^{2}-3x}\rightarrow$ $D=(-\infty,0)\cup(3,+\infty)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.